Layanan Bimbingan Konseling pada Klien Pemasyarakatan - Muhammad Najib Daroini; Lalu Satria Utama; Mukhlis Hafel (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to design an optimal Counseling Guidance Service model to maximize Counseling Guidance Services and suit the needs of Class II Fakfak Fathers by considering the obstacles and factors that support the counseling service. This research uses a qualitative approach with a case study method. This research was conducted at the West Papua Ministry of Law and Human Rights Regional Office. Data collection techniques include observation, interviews, questionnaires, and descriptive statistical data analysis techniques. The results of this research were obtained from interviews conducted with the head of the department and several other officers, namely the Correctional Center, who provided guidance and counseling services to teachers and former compensation. Counseling guidance services for clients are currently not optimal because there are still many deficiencies both in the human resources sector and in terms of office facilities; the counseling guidance service is not yet by the existing SOP because there are still many shortcomings. In conclusion, the counseling guidance service for Bapas Class II Fakfak is not optimal, and there are still many shortcomings because there are several facilities that fathers still need to have. Keywords: Communication, Employee Performance, Ethical Leadership Kata Kunci : Bimbingan Konseling, Pemasyarakatan.